2020
DOI: 10.3390/biom10020325
|View full text |Cite
|
Sign up to set email alerts
|

Current Advances in Allosteric Modulation of Muscarinic Receptors

Abstract: Allosteric modulators are ligands that bind to a site on the receptor that is spatially separated from the orthosteric binding site for the endogenous neurotransmitter. Allosteric modulators modulate the binding affinity, potency, and efficacy of orthosteric ligands. Muscarinic acetylcholine receptors are prototypical allosterically-modulated G-protein-coupled receptors. They are a potential therapeutic target for the treatment of psychiatric, neurologic, and internal diseases like schizophrenia, Alzheimer’s d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…In the established animal models, drugs have been used that block all five muscarinic receptor subtypes, hence, their systemic administration may induce side-effects in various organs [ 19 ]. The use of recently developed selective ligands for individual muscarinic receptors may reduce the systemic side effects [ 14 , 20 ], but is not likely to reduce the invasiveness and challenges of repeated drug administration. The use of genetically modified mice lacking individual muscarinic receptor subtypes may circumvent these problems.…”
Section: Discussionmentioning
confidence: 99%
“…In the established animal models, drugs have been used that block all five muscarinic receptor subtypes, hence, their systemic administration may induce side-effects in various organs [ 19 ]. The use of recently developed selective ligands for individual muscarinic receptors may reduce the systemic side effects [ 14 , 20 ], but is not likely to reduce the invasiveness and challenges of repeated drug administration. The use of genetically modified mice lacking individual muscarinic receptor subtypes may circumvent these problems.…”
Section: Discussionmentioning
confidence: 99%
“…The cholesterol-binding site(s), on the other hand, is oriented towards membrane and may bind membrane soluble compounds that share structural similarity with cholesterol, like steroid hormones or neurosteroids (NS). This site may represent a novel target for allosteric modulation of muscarinic receptors 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The common allosteric binding site of muscarinic receptors has been located between the second and third extracellular loop 10 . In contrast, the cholesterol-binding site is oriented towards membrane and may represent a novel target for allosteric modulation of muscarinic receptors with therapeutic potential 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Muscarinic receptors (M 3 ) associated with the pancreatic β-cell membrane help for the liberation of glucosedependent insulin, which is triggered by acetylcholine (Jakubik and El-Fakahany, 2020). The report found that intraperitoneal administration of OA in Wistar rats results in decreases in fasting glycemia with subsequent action of enhancing the plasma insulin level in a parallel manner which suggests OA has acetylcholine enhancing effect at nerve endings.…”
Section: Role Of Oa In M3 Receptormentioning
confidence: 99%